Identification of electric vehicle adoption and production factors based on an ecosystem perspective in Indonesia - Triyono Widi Sasongko; Udisubakti Ciptomulyono; Budisantoso Wirjodirdjo; Andhika Prastawa (Cogent Business & Management, 2024)
The program to replace fossil fuels powered vehicles with electric vehicles (EVs) is part of the global endeavor to reduce greenhouse gas emissions. In Indonesia, EV adoption is still low. The EV market share is currently 1.47 percent of the 10 percent goal for 2022. Due to the vulnerability of local industries, including electric vehicle (EV) startup manufacturers, foreign-origin equipment manufacturers (OEMs) continue to dominate the Indonesian automotive industry. Although the government encourages automakers to produce and sell battery electric vehicles (BEVs), the incumbent prefers to introduce hybrid electric vehicles (HEVs) and continues to prioritize internal combustion engine vehicles (ICEVs). Numerous studies have investigated the factors of EV adoption based on user perspective. However, few studies examine the factors influencing automakers to produce EVs, especially in developing nations like Indonesia, where foreign OEMs dominate automotive manufacturers. This study analyzes the drivers and barriers to adopting and producing electric vehicles from an ecosystem perspective, including users, the EV industry, charging infrastructure providers, and the government using the Delphi method. According to the findings, in addition to the user's ability and price barriers in the most demanded 7-seater EVs, the critical adoption and production factors are the effect of the OEM's global strategy and the priority of government policies to promote EVs while maintaining the sustainability of the automotive industry.
Keywords: 650; Electric vehicle; adoption; production; ecosystem; Delphi method; Indonesia